Collaborate to innovate - Goffin, Keith; Baxter, David; Schoeman, Magnus (Cranfield University School of Management, 2011)
Innovation is something that many governments strive to support, in both the private and public sectors. By bridging the two sectors and creating novel partnerships, public sector expenditure can be reduced.
Keywords: MT=IOM